Estimation the Relationship Between Vitamin D and Some Immune Parameters Among Patients with Graves’ Disease - Angham Jasim Mohammed Ali, Majedaldeen Jumaa Majeed Hamoud (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Graves’ disease is an autoimmune condition caused by thyroid-stimulating immunoglobulins binding to the thyrotropin receptor on the thyroid gland. This leads to increased thyroid hormone production, hyperthyroidism symptoms, and the development of diffuse goiter. Objectives: This research seeks to measure the concentrations of CD40, CD80, and CD86 in Graves’disease patients, as well as their vitamin D levels, and Determination the correlation between immunological markers by the (SPSS). Materials and Methods: This research included a total of (90) people of various sexes and ages (30 men and 60 females), including (60) Graves’ disease patients and (30) healthy people. Patients with Graves’ disease were seen at Alsader Medical City (Najaf Center for Diabetes and Endocrinology). Between November 2021 and January 2022. Results: The mean blood levels of Vitamin D revealed a very significant association (P.value> 0.005) across the groups tested for Graves ’ disease. The patients group comprised 20 men (33.3%) and 40 females (66.7%) and their mean CD40 serum levels were (36.89± 30.50 ng / ml) in the patients and 46.61± 16.14 ng / L in the controls. Conclusion: The Thyrotropin receptor antibody (TRAb) test and ultrasonography of the thyroid gland are useful diagnostic tools for autoimmune Graves’ disease (GD) since they may diagnose AITD early. Graves’ illness is connected with decreased vitamin D levels in the blood.